2018
DOI: 10.1093/ndt/gfy227
|View full text |Cite
|
Sign up to set email alerts
|

Persistent decrease of renal functional reserve in patients after cardiac surgery-associated acute kidney injury despite clinical recovery

Abstract: Among elective cardiac surgery patients, AKI or elevated post-operative CCA biomarkers were associated with decreased RFR at 3 months despite normalization of serum creatinine. Larger prospective studies to validate the use of RFR to assess renal recovery in combination with biochemical biomarkers are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 37 publications
2
44
0
1
Order By: Relevance
“…Our results show a positive treatment impact on sepsis survival with delayed administration of UPHD186, together with increased indicators of tissue proliferation and reduced fibrosis. Interestingly, serum creatinine and cytokines were insensitive to these pathological features-consistent with clinical observations [6,7]. Maladaptive repair and fibrosis are important mechanisms leading to CKD, apparently across AKI syndromes.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our results show a positive treatment impact on sepsis survival with delayed administration of UPHD186, together with increased indicators of tissue proliferation and reduced fibrosis. Interestingly, serum creatinine and cytokines were insensitive to these pathological features-consistent with clinical observations [6,7]. Maladaptive repair and fibrosis are important mechanisms leading to CKD, apparently across AKI syndromes.…”
Section: Discussionsupporting
confidence: 77%
“…Often, this relationship is obvious-CKD results when renal function remains low following an AKI episode. However, more complicated patterns of recovery following AKI have been reported [7] and concerns have been raised that renal functional recovery may belie ongoing insidious injury or progression [6]. Thus, AKI may develop into CKD, even in the cases where there is an appearance of renal recovery measured by conventional renal indicators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 To overcome this problem, it would be necessary to identify a marker able to detect a renal damage even in the absence of GFR alterations, discovering episodes of sub-clinical AKI 5 compensated by the renal functional reserve that can be lost after a pathological noxa, as heart surgery. 6 In this point of view, in the last years, several studies focused on the identification of new biomarkers including neutrophil gelatinase-associated lipocalin (NGAL), interleukin-18 (IL18), liver-type fatty acid binding protein (L-FABP), kidney injury molecule-1 (KIM-1), tissue inhibitor of metalloproteinases-2 (TIMP-2), and insulin-like growth factorbinding protein 7 (IGFBP-7). 7,8 In this spectrum of new markers, urinary insulin-like growth factor-binding protein (IGFBP-7) and tissue inhibitor of metalloproteinase (TIMP-2) have been proven as the best-performing.…”
Section: Introductionmentioning
confidence: 99%
“…The NC urinary biomarker appears to be more of a kidney ''stress'' indicator, although recent evidence has suggested that patients with NC elevations have some evidence of long-term decrease in renal functional reserve (the normal increase in glomerular filtration rate after a protein load). 4 Just as importantly, this test had a 100% negative predictive value, as none of those patients with a negative NC went on to develop significant AKI postoperatively.…”
mentioning
confidence: 96%